Adsorption of Iron Ions by Biocharcoal from Areca Nut Shells and Fruit Clusters - Hesti Rebo; Daud K. Walanda; Mery Napitupulu; Vanny M. A. Tiwow (Jurnal Akademika Kimia, 2024)
This study aims to identify the adsorption of iron ions by biochar produced from palm nut shells and palm fruit bunches. The method used in this study was a laboratory experiment employing palm nut shell biochar and palm fruit bunch biochar as adsorbents for Fe ions. The results showed that the optimum contact time for palm nut shell biochar was 150 minutes, with an iron ion adsorption percentage of 99.87%. In contrast, for palm fruit cluster biochar, the optimum contact time was 120 minutes, with an iron ion adsorption percentage of 99.83%. The optimal adsorption of iron ions by areca nut shell biochar occurred at a dose of 20 mg, with an adsorption percentage of 99.70%. In contrast, for areca fruit bunch biochar, it occurred at a dose of 40 mg, with an adsorption percentage of 99.80%. The optimal concentration obtained for both biochar types was the same, namely 60 ppm, with an iron ion adsorption percentage of 99.5% for areca nut shells and 98.85% for areca fruit bunches. The maximum adsorption capacity of areca nut shell biochar was 121.9512 mg/g, and that of areca fruit cluster biochar was 58.1395 mg/g, calculated using the Langmuir isotherm equation. Meanwhile, the maximum adsorption capacity of palm shell biochar was 123.0915 mg/g, and that of palm fruit bunches was 62.1871 mg/g using the Freundlich isotherm equation.